Biodegradation of Crude Oil in Contaminated Water by Local Isolates of Enterobacter cloacae - W. Ahmed, Ausama; S. Alzubaidi, Fawzi; J. Hamza, Subhi (Iraqi Journal of Science, 2023)
This paper study the ability of Enterobacter cloacae for degrading crude oil in contaminated water. Six isolates of E. cloacae were isolated from hydrocarbon contaminated soil and water of different sites. The isolate E. cloacae E1 showed the highest emulsification index (E24%) reached 62% thus it was chosen for further study. Biosurfactant produced by E. cloacae E1 reduced the surface tension of the medium from 64 to 36 mN/m. pH range 6.5 – 7 and temperature range 30˚C - 35˚C were the optimal conditions for maximum degradation. After 30 days of incubation, E. cloacae E1 degraded 70.00 ± 0.40% of the crude oil. GC-MS analysis revealed that E. cloacae E1 was able to degrade aromatic compounds. This study proved that E. cloacae E1 consider being an efficient in crude oil degradation.